A PROPOSAL OF PHILOSOPHY BEYOND THE VERBAL SPHERE FOR A DECOLONIZED THOUGHT - Garcia, Amanda Veloso [UNESP] (Univ Fed Reconcavo Bahia, Centro Formacao Professores, 2019)
This thesis investigated the relation between philosophy and the practice of writing texts in order to treat the following issue: There are alternative ways of expression and development of philosophy beyond those related to resources of verbal language? As there seems to be a necessary connection between philosophy and verbal language in the Western philosophical tradition, we aim to rethink philosophical practices within the university and to analyze the existing potential of various formats of thinking Initially, we present the contributions of an inter/multidisciplinary approach to philosophy, pointing to the paradigm of complexity as an appropriate resource for investigating contemporary philosophical problems. We understand that the complexity paradigm has been designed to provide a shift in philosophy that takes it beyond the realm of verbal language. As a case study, we discuss the central features of Brazilian philosophy in the context of the public university. In this context, we analyze the limits of verbal language as an expression of thoughts. Finally, we discuss the potential of non-verbal forms in philosophical reflection, analyzing their contributions and limits for the development of genuine philosophizing.
Keywords: Non-verbal language; Coloniality; Brazilian Philosophy